Bacteriophage P2. Issue 1 (2nd January 2016) - Christie, Gail E.; Calendar, Richard
ABSTRACT: P2 is the original member of a highly successful family of temperate phages that are frequently found in the genomes of gram-negative bacteria. This article focuses on the organization of the P2 genome and reviews current knowledge about the function of each open reading frame.